Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia (PMRI) Terhadap Kemampuan Pemecahan Masalah Matematis Berdasarkan Self-Esteem Siswa SD - Mentari, Mentari; Kesumawati, Nila; Hera, Treny (Indonesian Research Journal on Education, 2023)
This study aims to determine the effect of the PMRI approach on mathematical problem-solving skills based on the self-esteem of students at SD Negeri 31 Palembang. This research method is quasiexperimental. The research population is from grade 1 to grade 6 SD Negeri 31 Palembang. The sample used is the experimental class V.a totaling 26 students and the control class V.b totaling 25 students. The sampling technique in this research is random sampling. The treatment design was a posttest-only control design. data collection techniques in the form of questionnaires and tests. The data collection technique was two-way ANOVA with a significance of 0,05. The result of this research is that there is a significant effect of the PMRI approach on mathematical problem-solving ability. There is a significant difference in the average mathematical problem-solving ability based on self-esteem. there is a significant interaction between learning approaches and self-esteem there is a mathematical problem-solving ability.